PENAWARAN TEH HERBAL (Tisane) BAWANG DAYAK DI KELURAHAN JAHAB KECAMATAN TENGGARONG - Astik Drianti (Agriculture Faculty, University of Kutai Kartanegara, Indonesia, 2019)
The objectives of this study is to determine supply equation and supply elasticity from dayak onion tisane. This tisane supply equation is Y = 28,4175.X1 0,581741.X20,156042.X30,838484 with 60% significant factor on models. Supply elasticity 0,581741 and complementary relation with lemon grass tisane. Keywords : Tisane, Dayak Onion, Supply